An Overview of Mothers' Knowledge and Skills in Administering Tepid Water Sponge to Hyperthermic Children in Kalikidang Village - Fadhilla Noor Hidayah; Atika Dhiah Anggraeni (UM Purwokerto Press, 2026)
Background: Hyperthermia is an increase in body temperature that can be caused by hormonal disturbances, metabolic disorders, drug use, increased environmental temperature, or exposure to external heat, leading to an imbalance between heat production and heat loss in the body. Tepid Water Sponge is a procedure aimed at enhancing heat loss control through evaporation and conduction in individuals experiencing high fever. Method: This research employs a descriptive explanatory method with a total of 40 mothers as respondents. Data collection was conducted using a knowledge questionnaire and an observation sheet for skills assessment. Results: The study revealed that 63.4% of mothers had good knowledge, and 34.1% had adequate knowledge. Regarding tepid water sponge skills, 26.8% of mothers demonstrated a good understanding of the technique, 65.9% had adequate skills, and 4.9% had poor skills. Conclusion: Mothers' knowledge about tepid water sponge is generally good, although there are still a few (two mothers) who lack sufficient skills.